The Influence of the Characteristics of the Board of Directors and the Sharia Supervisory Board on the Risks of Islamic Commercial Banks in Indonesia - Indria Puspitasari Lenap; Baiq Krisnina Maharani Putri; Elin Erlina Sasanti (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to examine the characteristics of the Board of Directors (BoD) and the Sharia Supervisory Board (SSB) on the risk of Islamic commercial banks in Indonesia. This study is an associative study with a quantitative approach. The data used are secondary data in the form of annual financial report data and GCG reports of Islamic commercial banks. Based on purposive sampling technique, the sample of this study consists of 12 Islamic commercial banks listed with the Financial Services Authority (OJK) that published annual financial reports and GCG reports continuously for 5 years from 2019-2023. The results of the study indicate that female board of directors have a negative effect on Non-Performing Financing (NPF). In addition, the study found that age of the BoD has no effect on NPF, while the level of education and competence of the SSB have a negative relationship but do not have a significant effect on NPF. This study implies that Islamic banks in Indonesia need to strengthen the role of the BoD as the highest level of management, especially the existence of female BoD in Islamic commercial banks regarding their function in managing problematic financing risks. Moreover, increasing SSB competence through certification will support SSB performance to maximize the implementation of effective sharia governance